2022
DOI: 10.47391/jpma.3999
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vocal tract discomfort in patients with voice disorders

Abstract: Objective: To analyse the prevalence of vocal tract discomfort in patients with voice disorders. Method: The analytical cross-sectional study was conducted at Riphah International University, Lahore, Pakistan, from September 2020 to January 2021, and comprised voice disorder patients of either gender aged 18-65 years enrolled from Mayo Hospital, Sheikh Zayed Hospital and Jinnah Hospital, Lahore. The Vocal Tract Discomfort Scale was used for data-collection. Data was analysed using SPSS 21. Results: Of the 137 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
1
0
0
Order By: Relevance
“…In our study, the most prevalent cause of dysphonia between studied patients was organic lesion (22.8%) followed by non-organic (functional) causes (15.5%). In agreement with our study; Nawaz et al (17) found that organic lesions were the most common condition (67.9%), followed by functional disorders (22.6%), and neurological and psychogenic illnesses were the least common.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the most prevalent cause of dysphonia between studied patients was organic lesion (22.8%) followed by non-organic (functional) causes (15.5%). In agreement with our study; Nawaz et al (17) found that organic lesions were the most common condition (67.9%), followed by functional disorders (22.6%), and neurological and psychogenic illnesses were the least common.…”
Section: Discussionsupporting
confidence: 93%
“…This is in compliance with another local study which showed significant association of VTDS with gender as higher scores for females. 15 The present study did not reveal significant association of speciality being catered to with VTDS and VAPP; however, scores were higher for SLPs catering to cerebral palsy children. A study by Mozzanica F et al revealed more vocal load in SLPs treating clients with hearing impairment and phonation disorders compared to clients suffering from language disorders.…”
Section: Discussioncontrasting
confidence: 92%
“…Another study also revealed that the most affected (70%) age group was 18-33 years. 15 The present study reported significant (p=0.008) association of experience with VAPP with highest scores between 1-5 years, while no significant association was noted with VTDS.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation